Integrasi Fuzzy AHP-TOPSIS dalam Evaluasi Kualitas Layanan Elektronik Rumah Sakit - Ronald Sukwadi; Ching-Chow Yang; , Benny (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2014)
In today’s global era, the electronic service quality (E-SQ) development has swept across almost all service sectors. This development represents not only a new paradigm for providing services, but also a weapon for winning competitions. This research aims to examine and determine the key service attributes of E-SQ which is adopted from service quality (SERVQUAL) methodology as the reference model. The proposed E-SQ framework will be illustrated with a web service performance example of some public and private hospitals in Indonesia by integrating fuzzy analytic hierarchy process (AHP) and technique for order performance by similarity to ideal solution (TOPSIS). Finally, this study shows the implementation of the E-SQ framework in evaluating the complexity of service attributes observed in the hospital healthcare services via websites.